The impact of the light tube and the distance of the light trap from a stream on a caddisfly (Insecta: Trichoptera) catch - Gorazd Urbanič (Natura Sloveniae)
The author studied the impact of the light tube and the distance of the light trap from the Poltarica stream on a caddisfly catch. Four light traps, containing blacklight and bluelight tubes, respectively, were placed at different distances from the stream bank. The most efficient was the light trap placed 10 m away, followed by the light trap at the stream bank and the light trap 50 m away. However, males of the most abundant species Potamophylax cingulatus, which belonged to two subspecies, showed different distributional pattern. Among the used light traps, the one containing bluelight tube was less efficient than those with blacklight tubes.